Representation of Language, Ideology and Power in Pakistani Budget Speeches 2016- 2021 - Ahmad, Sidra (2023)
Politics is a discipline which involves common man and politician at same level apparently; the language of this field is normally termed political discourse. Generally, all speeches either they are victory, inaugural, parliament, election campaign or budget are included in political discourse; hence, politicians design their speeches considering their objectives important not the needs of their people. They do not present the neutral picture of their plans, goals, intentions and ideologies in speeches rather their words are multi-layered and dubious. Therefore, the present study objectifies to analyse Pakistani budget speeches on three levels e.g. (i) to investigate the textual discourse through the representation of language use, ideology and power in Pakistani budget speeches (ii) to synthesize discourse practices through the representation of language use, ideology and power in Pakistani budget speeches (iii) to develop the social practices through the representation of language use, ideology and power in Pakistani budget speeches from 2016-2021. The present research is a mixed method research for it involves qualitative and quantitative paradigm because the frequencies have been taken through software and the features have been studies through actual instances. The analysis has been conducted through three-dimensional model given by Fairclough (1995). Moreover, to investigate the objectives distinctly, two separate corpora of Pakistani budget speeches have been complied viz. from 2016 to 2018 one corpus and from 2019 to 2021 the other corpus. The reason behind forming two corpora was that these speeches were delivered by two different political speeches as, speeches from 2016 to 2018 have been declared by Pakistan Muslim League-Noon (PML-N) and from 2019 to 2021 have been presented by Pakistan Tehreek-e-Insaaf (PTI). At next step, both the corpora have been tagged through CLAWS tagger C7 to select the certain parts of speech and additionally, a software named Antconc has been used to get the accurate frequencies of certain words and to make the results more impartial. Each objective of has been attained through a detailed manual analysis of each category. Every category has been decisively set on the basis of chosen words from data. The study justifies the objectives very explicitly; in Pakistan, both the parties declare budget on same pattern which indicates that in Pakistani context politicians have their own set objectives which they attain through language use, by practicing power and promote their own ideology. Besides this, it also reveals that although, the speeches have been delivered in different years by different finance ministers but the dilemma is that no change occurred in budget discourse. Conclusively, the study portrays too that both the governments have their own goals which they have surely attained in their tenures. As, the study is pioneer in the domain of budget discourse therefore, the research is significant because it opens brand new ways to analyse budget speeches. Furthermore, a model has been generated to analyse budget discourse based on 3D model that is the most striking feature of this study and this model will be used in future to analyse the said speeches from different perspectives namely: Budget Speeches of all political parties, budget of different countries, choose large size of data, apply other models of CDA, budget of developing and developed countries, phrase and clause formation and different levels of linguistics (see 5.5).